Hubungan Penyesuaian Diri Dengan Agresivitas pada Anggota TNI AD KODAM IX/UDAYANA di Bali - Aditya Pratama Oktaveriyanto; David Hizkia Tobing (Jurnal Psikologi Udayana, 2016)
Behavior reflects the aggressiveness of the individual, as often occurs in Indonesia. One of many events has reflected the aggressiveness of the Army’s members. These events make the people become restless. A member of the Army in a period of education is trained hard, discipline, and will obey the command, in order to be prepared to maintain the sovereignty of the Unitary Republic of Indonesia (NKRI). This situation is not only giving an impact to the members of the Army, but also for their social interaction. A member of the army must be ready placed anywhere and anytime accordance with the instructions given by the institution. One of the factors that can affect the aggressiveness is adaptability. The purpose of this study is to determine whether there is a relationship between adjustment and aggressiveness to the Army KODAM Members IX/Udayana, in Bali.Subjects of this study were 439 members of the Army KODAM IX/Udayana in Bali which consists of eight entities supervised by the institution KODAM IX/Udayana. The instrument of this research is the scale of adjustment and scale of aggressiveness that has tested the validity and reliability of the scale and has a scale adjustment to the value of ? = 0.856; aggressiveness scale with the value ? = 0.913.The analysis showed the P value or Sig. 0.000 (p <0.05), which means that there is a significant relationship between the adjustment to the aggressiveness of the Army KODAM IX/Udayana members in Bali. Score correlation coefficient between the two variables showed R= -0.562 which means that the strength of the relationship between the two variables in a medium category, as the value of r lies in the range 0.400-0.599, and has a negative relationship or in opposite directions. R²= 0.31472, means that the variable adjustment donated 31% of the variable aggressiveness Keywords: Adjustment, Aggressiveness, Members of the ArmyKODAMIX/UDAYANA in Bali